フジ コウロ 1977-1978 ニオケル ヒョウメン カイスイ チュウ ノ クロロフィル aリョウ - 神田, 啓史; カンダ, ヒロシ; 福地, 光男; フクチ, ミツオ; KANDA, Hiroshi; FUKUCHI, Mitsuo (国立極地研究所, 1979)
P(論文) 1977年11月から1978年4月まで,第19次日本南極地域観測隊の海洋生物定常観測の一環として,「ふじ」の航路に沿って表面海水中のクロロフィルa濃度の測定を143点において実施した。南極大陸沿いの海域にて高濃度が見られ,プリンスオラフ海岸沖にて最高値(2.48 mg/m^3)が記録された.観測データは,今回はじめて電子計算機によるデータベースシステムによって処理された. During the relief cruise of the FUJI to Syowa Station, Antarctica, from November 1977 to April 1978, the chlorophyll a concentrations of the surface water were measured at 143 stations as a part of the routine observations of marine biological program of the 19th Japanese Antarctic Research Expedition. The high chlorophyll a concentrations were observed along the Antarctic Continent and the maximum value was recorded of the Prince Olav Coast, Antarctica (2.48 mg chl. aim^3). The attempt to use the computer for data processing was made for the first time. departmental bulletin paper